Penerapan Supervisi Klinis Untuk Meningkatkan Kinerja Guru di Masa Pandemi Covid-19 - Johora (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
The aims to improve teacher performance at SDI Barai 2 through clinical supervision during the covid-19 pandemic. This research is a school action research. The research subjects were teachers in elementary schools, totaling 6 (six) classroom teachers. For teacher performance data collected using some ways; they are observation, interviews, and documentation. The data analysis technique used was a descriptive analysis. The indicators of the success of this research are: if the average teacher performance is at least in the high category, and classical completeness is 90 percent. Based on the findings, the conclusion is that: applying clinical supervision can improve the performance of teachers in SDI Barai 2 effectively.